2015
DOI: 10.1007/978-3-319-22698-9_10
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Practices and Challenges Specific to International User Studies

Abstract: Abstract. In today's globalized world, it is increasingly important for comp anies to gain knowledge about international markets and to understand the differences and similarities between international users. As a result, international user studies have become more common. However, they still pose a challenge for most companies. In this paper, we present the results of an empirical investigation of how comp anies conduct international user studies. We describe the empirical findings in detail, with an emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…There seems to be an increasing interest in creating international personas by a growing number of UX designers (Madsen et al 2015). The objective of this paper has therefore been to contribute with an empirical study and meta-theoretical reflections on further work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There seems to be an increasing interest in creating international personas by a growing number of UX designers (Madsen et al 2015). The objective of this paper has therefore been to contribute with an empirical study and meta-theoretical reflections on further work.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the research project "International User Studies: How companies collect and represent data about users on international markets" (Madsen et al 2015), was to investigate how companies collect and present data about users in international markets. The research was initiated based on the literature review described above, which showed that more knowledge about how to conduct international user studies was required.…”
Section: A Presentation Of Our Danish Studymentioning
confidence: 99%